Production of the Polyhydroxyalkanoate PHBV from Ricotta Cheese Exhausted Whey by Haloferax mediterranei Fermentation - Susanna Raho; Vito Emanuele Carofiglio; Marco Montemurro; Valerio Miceli; Domenico Centrone; Paolo Stufano; Monica Schioppa; Erica Pontonio; Carlo Giuseppe Rizzello (Foods, 2020)
In the last decade, the dairy industry underwent a rapid expansion due to the increasing demand of milk-based products, resulting in high quantity of wastewater, i.e., whey and ricotta cheese exhausted whey (RCEW). Although containing high content of nutritional compounds, dairy by-products are still disposed as waste rather being reintroduced in a new production chain, hence leading to environmental and economic issues. This study proposes a new biotechnological approach based on the combination of membrane filtration and fermentation to produce poly-hydroxyalkanoates (PHA), biodegradable bioplastics candidate as an alternative to petroleum-derived plastics. The protocol, exploiting the metabolic capability Haloferax mediterranei to synthesize PHA from RCEW carbon sources, was set up under laboratory and pilot scale conditions. A multi-step fractionation was used to recover a RCEW fraction containing 12.6% (w/v) of lactose, then subjected to an enzymatic treatment aimed at releasing glucose and galactose. Fermentation conditions (culture medium for the microorganism propagation, inoculum size, time, and temperature of incubation) were selected according to the maximization of polymer synthesis, under in-flasks experiments. The PHA production was then tested using a bioreactor system, under stable and monitored pH, temperature, and stirring conditions. The amount of the polymer recovered corresponded to 1.18 g/L. The differential scanning calorimetry (DSC) analysis revealed the poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) as the polymer synthesized, with a relatively high presence of hydroxyvalerate (HV). Identity and purity of the polymer were confirmed by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) and X-ray photoelectron (XPS) spectroscopy analyses. By combining the fractionation of RCEW, one of the most abundant by-products from the agri-food industry, and the use of the halophile Hfx mediterranei, the production of PHBV with high purity and low crystallinity has successfully been optimized. The process, tested up to pilot scale conditions, may be further implemented (e.g., through fed-batch systems) and used for large-scale production of bioplastics, reducing the economical and environmental issues related the RCEW disposal.